The Mischievous Typesetter - Loomis, Noel M., 1905-1969; Terry, W. E., 1921-1992 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Mischievous Typesetter" by Noel M. Loomis is a short science fiction story likely written in the early 1950s. The narrative revolves around High-Pockets Jones, a linotype operator, who finds himself at the mercy of a malfunctioning linotype machine that seems to have developed a will of its own. Through a blend of humor and surrealism, the story explores the relationship between man and machine, emphasizing themes of control, understanding, and the unexpected capabilities of technology. In the story, High-Pockets is sentenced by a judge to work on a troublesome linotype, known as No. 7, which has been causing chaos in the composing room of the Daily News. As he attempts to tame the unruly machine, High-Pockets discovers that No. 7 not only acts independently but also seems to respond to his emotional state and intentions. Throughout the chaotic night, he battles both the machine's unpredictable behaviors and his own distractions, often fueled by alcohol. The climax of the story culminates when High-Pockets realizes that the linotype's uproar is not merely mechanical but tinged with a sense of personality and spirit, leading to a comedic and thought-provoking confrontation where the dynamics of authority and machinery intertwine. (This is an automatically generated summary.)
Release date is 2021-07-18
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Linotype -- Fiction